Nanosistemas de penicilina G benzatina para tratamento profilático da febre reumática: estudo analítico - Silva, Kattya Gyselle de Holanda e (2006)
Investigations in the field of pharmaceutical analysis and quality control of medicines require analytical procedures with good perfomance characteristics. Calibration is one of the most important steps in chemical analysis, presenting direct relation to parameters such as linearity. This work consisted in the development of a new methodology to obtain calibration curves for drug analysis: the stationary cuvette one. It was compared to the currently used methodology, and possible sources of variation between them were evaluated. The results demonstrated that the proposed technique presented similar reproducibility compared to the traditional methodology. In addition to that, some advantages were observed, such as user-friendliness, cost-effectiveness, accuracy, precision and robustness. Therefore, the stationary cuvette methodology may be considered the best choice to obtain calibration curves for drug analyis by spectrophotometry